(untitled) (African Journal of Biomedical Research, 2022)
Cancer is a public health menace with high rate of mortality, especially in developing countries. The condition as well as its therapy may negatively affect the immune system of its patients thereby predisposing them to opportunistic infections, including parasitic diseases with management problems. To investigate the intestinal parasite status and CD4 levels of cancer patients visiting a Tertiary Hospital, in Calabar, Nigeria, hence proffer solution to the cancer management problems. A cross sectional [study design was employed with 317 stool and blood samples, each collected from 186 confirmed cancer and 131 non-cancer patients (apparently healthy individuals). Direct microscopy and formol ether concentration techniques were employed for the examination and identification of stool parasites. BD-fascount technique for CD4 count. Data were analyzed with statistical package for social sciences (SPSS) version 25.0 using Chi-square and t-test, respectively at P < 0.05 and 95% confidence interval. The overall prevalence of intestinal parasites in this study was 87(27.44%) with significantly higher prevalence seen in cancer 65(34.9%) than in non-cancer subjects 22(16.8%), (X2 =12.72, P<0.001). Subjects with choriocarcinoma recorded the highest occurrence of intestinal parasites. Mean CD4 level was significantly lower in cancer patients (589.30±333.83) than in non-cancer subjects (703.37±290.86) (t=3.157, P=0.002). Parasite infected cancer subjects had significantly lower mean CD4 counts than their non-infected counterpart (543.86±299.41 versus 617.79±349.11 cells/ul), respectively (t = 1.445, P = 0.001). Parasite species detected in the study in order of their frequencies were hookworm 27(40.3%), Ascaris lumbricoides (34.3%), Trichuris trchiura (9.0%), Taenia spp (6.0%), Entamoeba histolytica/dispar (6.0%) and Strongyloides (4.5%). This study has confirmed that cancer lowers its host’s CD4 level either alone or in combination with intestinal parasites which may play etiologic orenhancement role in cancer development, with complications and management problems. Management of cancer cases should include parasitological diagnosis and treatment.